Limited Effects of Short-Term Heat Acclimation during a Rugby League Training Week - Mark Waldron (Archives of Physical Health and Sports Medicine, 2018)
We investigated the effects of five consecutive days of short-term heat acclimation (STHA), with a 48-h recovery,onsimulated rugby league performance, peakoxygen uptake (O2peak), physiological and perceptual responses in atemperate environment.Twelve male rugby league players took part in a matched-pairs design, cycling 60-min/day, for five days at 40% O2peak, in a control (19 ± 1C; 50 ± 3 % RH;n = 6) or STHA group (33 ± 0.5 C; 70± 4 % RH; n = 6). Subjects completed aO2peak test and rugby simulation, followed by a time-to-exhaustion,preand post-intervention, with physiological and perceptual responses measured during the interventions. Despiteno effect on simulatedperformance (P> 0.05), there were increases in time-to-exhaustion among both groups(P= 0.016), without group effects (P = 0.802). The STHA group adapted across the intervention, with lowertympanic temperature, perceptual responses and heart rate over time (P< 0.05),whichwere typically higherthan the control group (P< 0.05). Plasma volume did not increase over time or change between groups (P= 0.290) and O2peak reduced pre-to-post (P < 0.001).There was a relationship between body mass losses andplasma volume expansion (r = -0.79, P = 0.022). STHA improvedtolerance to the heatbut not performance insimulated matches or exhaustive tests in temperate conditions, compared to thermoneutralexercise. The limitedeffects of STHA might relate to the brief post-intervention recovery period or the lack of fluid ingestion controlduring acclimation.